Comprehensive safety and toxicity analysis of 2,2’-Bipyridine derivatives in combating MRSA biofilm formation and persistence - Priyanka; Sharma, Mohini; Vaid, Bhavna; Bharti, Ram; Raut, Sachin; Jolly, R. S.; Khatri, Neeraj (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMethicillin-resistant Staphylococcus aureus (MRSA) infections have become arduous to treat due to their capacity to form biofilms, develop persistence, and exhibit significant antimicrobial resistance. These factors contribute to the complexity of managing MRSA infections and highlight the urgent need for innovative treatment strategies.ObjectivesThis endeavor aims to evaluate the safety of 2,2’-Bipyridine (2,2’-Bipy) derivatives and their antimicrobial, anti-biofilm, and anti-persister activities in treating MRSA Infections.MethodsSix derivatives were screened for their ADMET properties and tested for minimum inhibitory concentrations against various bacterial strains using agar well diffusion and broth dilution. Safety studies were conducted through hemolysis tests, cell viability assays, and in vivo acute oral toxicity examinations. Bactericidal mechanisms and biofilm disruption effects were analyzed using crystal violet staining and confocal microscopy assays. The murine thigh infection model was also used to investigate the in vivo efficacy.ResultsAll derivatives exhibited favorable physicochemical profiles and ADMET properties and are predicted to be safe based on their drug-like properties. in vitro studies demonstrated that derivatives are non-toxic to 3T3 L1, and in vivo studies confirmed their safety in mice at a dose of 300 mg/kg and their non-hemolytic nature against rabbit red blood cells. All compounds showed potent antibacterial activity against the tested bacteria, including the resistant MRSA strain 831. They inhibited biofilm formation and eradicated biofilms in a dose-dependent manner against MTCC 737 and MRSA 831, and they effectively eliminated MRSA persister cells, outperforming the reference antibiotic vancomycin. These derivatives were found to depolarize the mitochondrial membrane and accumulate intracellular reactive oxygen species. These derivatives significantly reduced the bacterial load in the murine thigh infection model.ConclusionThe study concluded that 2,2’-Bipy derivatives possess significant antimicrobial activity, are non-toxic, and are effective in inhibiting biofilm formation and killing persister cells.